Estimating cumulative evapotranspiration using superconducting gravimeter data: a study in Buenos Aires Province, Argentina - Pendiuk, Jonatan Emmanuel (2023)
A new method for estimating cumulative evapotranspiration using superconducting gravimeter data is presented. Evapotranspiration is computed from the classical water balance equation using precipitation data, estimated runoff, and water storage assessed from temporal variations of gravity. The gravity-based methodology is applied to a study site located at the Argentinian–German Geodetic Observatory (AGGO) in the flatland area of Buenos Aires Province (Argentina), which houses the only superconducting gravimeter in South America. For the period from April 2017 to May 2018, the cumulative evapotranspiration is estimated at 710.7 ± 25.7 mm. Evapotranspiration values are successfully compared with estimates provided by three methods, based on the water balance equation using soil moisture data, the numerical modelling of water flow in the unsaturated zone and the MODIS product (MOD16A2). The analysis of evapotranspiration also allows us to identify a period of soil water stress which is validated by soil moisture measurements.